Nitrogen Distribution in Soil under Different Methods of Irrigation and Fertilizer Application - Ajdary, Khalil; Singh, D K; Singh, A K; Rajput, TBS; Khanna, Manoj (Journal of Agricultural Engineering, 2006)
A study was conducted on a sandy clay loam soil of IARI Farm to evaluate the nitrogen distribution in the soil under drip fertigation with onion crop. Five treatments with varying rate of recommended dose of nitrogen under drip irrigation, drip fertigation and basin irrigation were considered in the study. Results revealed that nitrogen distribution under drip fertigated treatments were mostly confined to the root zone. In case of drip-irrigated treatment with basal application of fertilizer and basin irrigation with basal application of fertilizer, nitrogen distribution showed the tendency of moving below the root zone. Temporal distribution of nitrogen indicated that depletion rate of nitrogen was highest during the third month of the growing season.